HUBUNGAN ANTARA DIAMETER BATANG DENGAN UMUR TANAMAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KELAPA SAWIT - Vika Yudistina; Mudji Santoso; Nurul Aini (Universitas Tribhuwana Tunggadewi, 2017)
Oil palm is a plant which is quite important commodities in Indonesia and still have a fairly bright development prospects Production of fresh fruit bunches (FFB) is the result of work activities in the field of plant maintenance. The success of FFB production depends by several factors, including environmental factors, the crop factor and factor cultivation purpose of this study was to determine and learn the age and size of the trunk palm trees both in achieving production, and Knowing how the relationship between stem diameter and plant age with results production of fresh fruit bunches (FFB). This study used 75 samples are grouped according to the age of the plant that is 2 years, 4 years, 6 years, 8 years and 10 years. Each sample was observed with 7 parameter pengamatanDari results of this study can be concluded that the larger the diameter of the stem of the plant oil palm as well as the age tanama or rather would affect positively correlated or significantly affected the production of oil palm plantation itself. All variables observation showed positive correlation with stem diameter relationship of age with less plant oil palm plantations. But there was one that did not happen correlation / negative correlations were age first fruit the size of a small diameter This is due to many factors such as rainfall is high enough to some areas or plantations are often flooded by rainwater, farming areas mostly are the tidal rivers, especially in 8 years old plantation blocks and handling of the plantation itself is still lacking.